2020
DOI: 10.1002/oby.22690
|View full text |Cite|
|
Sign up to set email alerts
|

Predicted Lifetime Third‐Party Costs of Obesity for Black and White Adolescents with Race‐Specific Age‐Related Weight Gain

Abstract: Original Article EPIDEMIOLOGY/GENETICS Study ImportanceWhat is already known?► Accounting for age-related weight gain causes a huge correction in the lifetime cost of obesity because of the tendency of normal-weight people to face obesity later in life. ► The relative cost of obesity is generally significantly higher for white males and females compared with their black counterparts. ► Age-related weight gain likely occurs fastest among black males and females, although there exist relatively few studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Compared with peers in other racial groups, black emerging adults have the highest risk for short sleep duration 3 16–18 and obesity, 19 20 but sleep data are limited to self-report 3 16–18 and actigraphy-based 21 measures. In addition, the CARDIA study reported excessive weight gain (defined as >20 kg) in 15%–22% of black emerging adults (compared with 6%–9% of white emerging adults), 20 and a recent report noted that black emerging adults face the prospect of obesity a full decade before their white counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with peers in other racial groups, black emerging adults have the highest risk for short sleep duration 3 16–18 and obesity, 19 20 but sleep data are limited to self-report 3 16–18 and actigraphy-based 21 measures. In addition, the CARDIA study reported excessive weight gain (defined as >20 kg) in 15%–22% of black emerging adults (compared with 6%–9% of white emerging adults), 20 and a recent report noted that black emerging adults face the prospect of obesity a full decade before their white counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the CARDIA study reported excessive weight gain (defined as >20 kg) in 15%–22% of black emerging adults (compared with 6%–9% of white emerging adults), 20 and a recent report noted that black emerging adults face the prospect of obesity a full decade before their white counterparts. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Childhood overweight and obesity (OVOB) is a global public health problem ( Di Cesare et al, 2019 ) associated with adverse physical and psychological health ( Berardis & Sokal, 2014 ; Quek, Tam, Zhang, & Ho, 2017 ) and lower educational outcomes ( Ma et al, 2020 ). As the condition continues to adulthood ( Ward et al, 2017 ), childhood OVOB is a risk factor for a range of chronic conditions ( Llewellyn, Simmonds, Owen, & Woolacott, 2016 ), leading to higher health costs ( Schell, Just, & Levitsky, 2020 ). While OVOB can affect children of all backgrounds, those born to migrants in developed countries tend to be disproportionately affected ( Hartono, Cochrane, Niyonsenga, & Kinfu, 2021 ; Zulfiqar, Burns, D'Este, & Strazdins, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is contrary to fact. Recent work by Fallah-Fini et al (2017) and Schell et al (2020) has found that age-related weight gainthe fact that a person's BMI tends to increase significantly as they age accounts for the majority of costs associated with obesity (Fallah-Fini et al, 2017;Schell et al, 2020). There are numerous other factors that explain the divergence of cost estimates between studies, including the selection of an appropriate cost model and accounting for differential life expectancy, that are essential to producing accurate and consistent estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Age-related weight gain is a persistent phenomenon found in the USA, where people tend to gain weight with a concomitant rise in adiposity as they age (Williams & Wood, 2006). Despite this fact, relatively few lifetime cost estimates of obesity factor age-related weight gain into their models (Finkelstein et al, 2008;Fallah-Fini et al, 2017;Schell et al, 2020). To understand the sheer complexity of modeling BMI development over time, it is instructive to think about what causes a person to develop obesity in their lifetime.…”
Section: Introductionmentioning
confidence: 99%